PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MOBIL MEREK ISUZU PANTHER PADA PT. ASTRA ISUZU SEMARANG - Ardhi Wahyu Saputra; Dina Lestari (Universitas Diponegoro, 2017)
Tranport equipment is badly needed in this era of fast-paced as it is, particularly cars. Competition in the automotive world is so tight. Therefore, businesses are required to be able to increase sales in order to survive in the business worlds. Specifically, this research was discuss about automobile buying of Isuzu Panther brand at PT Astra Isuzu Semarang during 2012-2015 keep have sale descending. If that case wasn’t improve and solve, probably will presense problem for PT. Astra Isuzu Semarang next.Aim of this research was to found brand image and product quality concerning automobile buying decision of Isuzu Panther Semarang. This research type was explanatory, with data collection technique by questionaire. The population in this research is consemers who use and bought Isuzu Panther automobile on PT Astra Isuzu Semarang with the number of samples taken was 72 respondents. Sampling using purposive sampling technique. Measurement scale using Likert scale. The analytical method used is the determination, simple linear regression, multiple liniear regression, t-test, and F-test using SPSS program version 16.Based on the results of the research, revealed that the partially, brand image and product quality has positive influence on the purchasing decision which is indicated by result of the value of t test bigger than t table. Significantly, variable brand image and product quality has positive influence towards purchasing decision indicated by value of F test larger than F table.And the advice that can be given is keeping a good image with a way keep it always communicate with consumers and customers. Besides continuing and improving product quality as well as improving its shortcomings, adding interior and exterior facilities and applying innovation to its products so as not to have the impression of monotonous and outdated